Vanadium Oxide Catalysts on Structured Microfiber Supports for the Selective Oxidation of Hydrogen Sulfide; Catalysis in Industry; Vol. 7, iss. 2 - Mikenin P. E.; Tsyrulnikov P. G.; Kotolevichb Y. S.; Kravtsov А. V. Anatoly Vasilyevich; Ivanchina E. D. Emilia Dmitrievna; Zagoruiko A. N. Andrey Nikolaevich (2015, 2015)
Title screen